Real-time system event monitoring display via Liquid Cristal Display (LCD) / Ahmad Safwan Abdul Aziz - Abdul Aziz, Ahmad Safwan (Faculty of Information Technology and Quantitative Sciences, 2006)
This research is about the development of system event monitoring and their information will be displayed on Liquid Cristal Display (LCD). Monitoring of computing systems in an organization is required to ensure proper functioning of system services by detecting inconsistencies in system configuration. Monitoring the system also will enable system administrator to predict and prevent problems that might make the system or its peripherals unavailable to users. This project mainly focuses on developing a prototype that can display system monitoring information on LCD display in a real time environment. The LCD panel is connected to the computer via parallel port. The function of LCD panel is to display the information that can be gathered by using software that have been develop called ‘LCD Panel Utilities’ to communicate with the LCD. The application has been developed by using Pascal programming language. The development process follows the six phases in systematic design are preliminary study, gathering and analyzing requirements, LCD front panel design, software design and coding, testing and maintenance. At the end of the development, the prototype of the application is come out and readily to be tested. For future researcher, some extra features can be added at an application. Some features such as the local system information can be added into the application. Future researcher also can make this application at another platform operating system such as Linux and MacOs. The LCD application on this project is working on local computer only, so that hope that the future researcher can make it as a server client application where the real time information of client computer can be gathered by remotely. In this project, we only use 2x16 LCD size, for future researcher, they can use bigger LCD size for displaying purposes.